In vitro effects of Melaleuca alternifolia essential oil on growth and production of volatile sulphur compounds by oral bacteria (Journal of Applied Oral Science, 2016)
Objective Halitosis can be caused by microorganisms that produce volatile sulphur compounds (VSCs), which colonize the surface of the tongue and subgingival sites. Studies have reported that the use of natural products can reduce the bacterial load and, consequently, the development of halitosis. The aim of this study was to evaluate the antimicrobial activity of the essential oil of Melaleuca alternifolia on the growth and volatile sulphur compound (VSC) production of oral bacteria compared with chlorhexidine. Material and Methods The effects of these substances were evaluated by the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) in planktonic cultures of Porphyromonas gingivalis and Porphyromonas endodontalis. In addition, gas chromatography analyses were performed to measure the concentration of VSCs from bacterial cultures and to characterize M. alternifolia oil components. Results The MIC and MBC values were as follows: M. alternifolia - P. gingivalis (MIC and MBC=0.007%), P. endodontalis (MIC and MBC=0.007%=0.5%); chlorhexidine - P. gingivalis and P. endodontalis (MIC and MBC=1.5 mg/mL). M. alternifolia significantly reduced the growth and production of hydrogen sulfide (H2S) by P. gingivalis (p